An Identity-Based Encryption Scheme with Performance Optimization for Privacy Preservation in Smart Grid Communication - Baloglu, Ulas Baran; Demir, Yakup (Iaria Xps Press, 2017)
Smart grids are expected to replace existing electrical grids with advanced mechanisms and intelligent entities, which have excessive data processing and communication tasks. It is important for the sensitive consumer data, such as meter readings, to be secured at these intelligent entities. Novel digital communication mechanisms should be developed to protect privacy. Existing smart grid architectures do not have sufficient and efficient security functionalities for data transmission. In this paper, we propose an Identity-Based Encryption scheme, which is more promising than the classical form regarding performance and security. The proposed scheme focuses on the data structure of meter readings and optimizes this structure to achieve a better privacy preservation. This novel structure further improves the performance of the scheme by reducing communication overhead caused by public key creation and distribution operations, as evaluations demonstrated.
12th International Conference on Digital Telecommunications (ICDT) -- APR 23-27, 2017 -- Venice, ITALY
Keywords: identity-based encryption; smart grid; privacy preservation